Post-Pandemic Profitability of Islamic Commercial Banks in Indonesia: Evidence from Financing Risk, Liquidity, Asset Quality, and Capital Adequacy - Nida Nadya Hasan; Elsafath Fadila Cahyaningrum (SAN Scientific, 2026)
This study examines the effects of Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), Productive Asset Quality (KAP), and Capital Adequacy Ratio (CAR) on the profitability of Islamic Commercial Banks in Indonesia, measured by Return on Assets (ROA), during the 2020–2023 post-pandemic period. The study addresses inconsistent findings regarding the effects of financing quality, liquidity, asset quality, and capital adequacy on profitability. The 2020–2023 period represents the post-pandemic recovery, characterized by shifts in financing demand, risk exposure, and digital transformation. A quantitative approach was employed using secondary data from the annual financial reports of 12 Islamic Commercial Banks published by the Financial Services Authority (OJK). Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that NPF, FDR, KAP, and CAR have no significant effect on ROA during the observation period. These findings suggest that Islamic bank profitability is influenced more by operational efficiency and macroeconomic conditions than by these financial ratios. This study provides updated evidence on the determinants of profitability and the resilience of Islamic banking performance in Indonesia during the post-pandemic recovery.